Vaccine effectiveness against influenza-associated hospitalizations in adults with liver disease, 2015–2020: US Hospitalized Adult Influenza Vaccine Effectiveness Network (HAIVEN) - Po-Han Huang; Mary Patricia Nowalk; Richard K. Zimmerman; Samantha M. Olson; H. Keipp Talbot; Yuwei Zhu; Manjusha Gaglani; Kempapura Murthy; Arnold S. Monto; Emily T. Martin; Fernanda P. Silveira; G.K. Balasubramani (Human Vaccines & Immunotherapeutics)
Influenza causes 100,000–710,000 hospitalizations annually in the U.S. Patients with liver disease are at higher risk of severe outcomes following influenza infection. This study evaluated influenza vaccine effectiveness (VE) against influenza-associated hospitalization among adults with liver disease. Data from the U.S. Hospitalized Adult Influenza Vaccine Effectiveness Network (HAIVEN), a test-negative case-control study, from 2015 to 2020 were used to estimate VE among adults ≥18 years admitted for acute respiratory illness. VE was calculated as (1-adjusted odds ratio)*100%, comparing the odds of vaccine receipt between laboratory-confirmed influenza cases and test-negative controls using multiple logistic regression with inverse probability of treatment weighting (IPTW). In total, 1,622 (12.8%) of 12,704 adults had ≥1 liver disease(s). Compared with those without liver disease, adults with liver disease were more likely to be admitted to the intensive care unit (15.7% vs 12.8%, p = .001) or to die in hospital (3.0% vs 1.4%, p < .001). The IPTW-adjusted VE against influenza-associated hospitalization was 27% (95% confidence interval [CI], 22–32%) among patients without liver disease, but the VE of 11% (95% CI, −8–26%) was not significant among those with liver disease. Significant effect modification of VE by the presence of liver disease was found (p < .05 for interaction term). While influenza vaccination significantly reduced the risk of influenza-associated hospitalization among adults without liver disease, the protective effect was not significant among those with liver disease. Further studies are warranted to evaluate influenza VE in patients with different types of liver disease and with specific vaccine formulations.